1993
DOI: 10.1002/cjce.5450710308
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modelling of the hydrolysis of carbonyl sulfide catalyzed by either titania or alumina

Abstract: The reaction rates for the hydrolysis of COS on both alumina (Kaiser 201) and titania (CRS 31) were measured from 270 to 330°C using a laboratory Berty reactor over ranges of water concentration, 2‐12 mol %, and COS concentrations, 0.5‐2 mol %. Four mechanism‐related model functions were tested in the search for the best fitting function by using nonlinear regression techniques. The results indicate that an Eley‐Rideal model provides the best fitting rate function for the hydrolysis of COS for both alumina and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 7 publications
2
22
0
Order By: Relevance
“…Tong et al [67] studied the hydrolysis of carbonyl sulfide under medium temperature conditions and concluded that the catalytic hydrolysis of carbonyl sulfide is a first-order reaction with respect to carbonyl sulfide, while the reaction order of water is influenced by the partial pressure of water. When the partial pressure of water is 0.1–0.26, the reaction order of water is 0.4.…”
Section: Reaction Kinetics Of Cos Hydrolysismentioning
confidence: 99%
“…Tong et al [67] studied the hydrolysis of carbonyl sulfide under medium temperature conditions and concluded that the catalytic hydrolysis of carbonyl sulfide is a first-order reaction with respect to carbonyl sulfide, while the reaction order of water is influenced by the partial pressure of water. When the partial pressure of water is 0.1–0.26, the reaction order of water is 0.4.…”
Section: Reaction Kinetics Of Cos Hydrolysismentioning
confidence: 99%
“…To simulate the performance of the catalytic converters in a modified Claus process plant, knowledge of the kinetics of the hydrolysis of CS2 or COS is needed. To date, the kinetics of hydrolysis of COS have been examined (Tong et al, 1993). This paper describes further results, obtained from a study of the kinetics of hydrolysis of CS2 over either alumina or titania catalysts.…”
mentioning
confidence: 99%
“…Therefore, under operating conditions close to industrial conditions, TiO 2 based catalysts seem to be more active than alumina catalysts. For example, this has been reported in a comparative study on commercial catalysts based on alumina (Kaiser-201, Kaiser Aluminum and Chemicals) and titania (CRS31, Axens) [91,92]. Concerning any kind of catalyst, the specific surface area is a key parameter, COS conversion rate being favored when catalyst surface increases [88].…”
Section: Cos Removalmentioning
confidence: 96%
“…Considering the activation energy, gamma alumina materials might be more active than TiO 2 materials [89,91], and should thus favor COS hydrolysis from lower temperature (T < 200°C). However, some experimental observations show the opposite; water, which is necessary to the reaction, can adsorb on catalyst surface and inhibit the catalytic activity.…”
Section: Cos Removalmentioning
confidence: 99%